2012
DOI: 10.1007/s12262-012-0707-1
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Study of Coeliac Trunk Specific Reference to Hepatic Artery Pattern in the West-Indian Population

Abstract: The aim of this study was to analyze anatomy of the celiac trunk through its diameter, length, and variation of its branches. We studied 40 cadavers (25 males and 15 females) in the various colleges in the west India for the variation in the celiac trunk. Dissection of the celiac trunk was performed after opening of the peritoneal cavity. The length of the celiac trunk up to the common hepatic artery was observed. Diameter of the celiac trunk and distance between the celiac trunk and the superior mesenteric ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 7 publications
0
14
0
1
Order By: Relevance
“…A study by Singh et al [ 30 ] observed a mean diameter of the celiac trunk of 6.6 mm, with a minimum 4 mm and maximum 10 mm. This finding is similar to the mean diameter in our study (7.2 mm, range from 6 to 12 mm) ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Singh et al [ 30 ] observed a mean diameter of the celiac trunk of 6.6 mm, with a minimum 4 mm and maximum 10 mm. This finding is similar to the mean diameter in our study (7.2 mm, range from 6 to 12 mm) ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Singh et al [15] measured the distance between the CT and the superior mesenteric artery, with regard to sex. The average distance between the arteries for both sexes was 8.1 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Familiarity with anatomic variations of the CT is relevant for planning radiological and surgical procedures in the abdominal part of the oesophagus, stomach, duodenum, liver, pancreas, gallbladder, and spleen [5,9,12,17,18]. Modern transplantology requires knowledge on vascular variations, including incidence of accessory hepatic arteries (AHA) [10,15]. Araujo Neto et al [2] also suggested that the coeliac trunk's diameter, as well as the distance between the trunk and the superior mesenteric artery should be estimated prior to a surgical procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Celiac trunk variations increase the difficulty and the risk of several surgical procedures, particularly laparoscopic cholecystectomy, liver resections, gastric resections, transplant surgery, and others. 8,9 Anatomic variations are crucial for surgeons and interventional radiologists; in relation to preoperative computed tomography, MRI, and intraoperative angiography. 10 We present an anatomical case report of unusual branching of the celiac trunk into five arteries and review its clinical importance.…”
Section: Introductionmentioning
confidence: 99%